2006
DOI: 10.1641/0006-3568(2006)56[757:argtig]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Rough Guide to Interdisciplinarity: Graduate Student Perspectives

Abstract: N atural and social scientists addressing complex ecological problems increasingly recognize the value of one another's research, and often seek multidisciplinary, interdisciplinary, or transdisciplinary approaches to investigate real-world issues. A multidisciplinary approach involves researchers from two or more disciplines working collaboratively on a common problem, without modifying disciplinary approaches or developing synthetic conceptual frameworks. An interdisciplinary approach involves the use of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(113 citation statements)
references
References 20 publications
0
107
0
2
Order By: Relevance
“…To start with the proposed frameworks, these publications considered the following teaching and learning topics: an adaptation of Biggs and Collis' Structure of Observed Learning Outcome (SOLO) taxonomy to illustrate interdisciplinary learning (Ivanitskaya et al 2002), a proposed research agenda based on teaching and learning theories to encourage research in the field of interdisciplinary higher education (Lattuca et al 2004), a framework illustrating three major cognitive movements in interdisciplinary thought (Nikitina 2005), three strategies for interdisciplinary teaching (Nikitina 2006), four dimensions of a potential interdisciplinary pedagogy (Manathunga et al 2006), an empirically grounded framework for assessing students' interdisciplinary work (Boix Mansilla and Duraising 2007), and a framework for conceptualizing interdisciplinary classroom communication (Woods 2007). Second, best practices dealt with the relationship between disciplinary background and interdisciplinary education (Newell 1992), with the lack of adequate and appropriate methods for assessing interdisciplinary higher education programs (Field and Lee 1992), with the experiences of graduate students who pursued interdisciplinary studies (Graybill et al 2006), and a successful course approach (Eisen et al 2009). Third, the following essential conditions were identified through the evaluation of two interdisciplinary training programs: participation, training in group skills, information sharing, networking, critical reflection (Gilkey and Earp 2006), participation in a collaborative interdisciplinary team project, and faculty mentors (Misra et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…To start with the proposed frameworks, these publications considered the following teaching and learning topics: an adaptation of Biggs and Collis' Structure of Observed Learning Outcome (SOLO) taxonomy to illustrate interdisciplinary learning (Ivanitskaya et al 2002), a proposed research agenda based on teaching and learning theories to encourage research in the field of interdisciplinary higher education (Lattuca et al 2004), a framework illustrating three major cognitive movements in interdisciplinary thought (Nikitina 2005), three strategies for interdisciplinary teaching (Nikitina 2006), four dimensions of a potential interdisciplinary pedagogy (Manathunga et al 2006), an empirically grounded framework for assessing students' interdisciplinary work (Boix Mansilla and Duraising 2007), and a framework for conceptualizing interdisciplinary classroom communication (Woods 2007). Second, best practices dealt with the relationship between disciplinary background and interdisciplinary education (Newell 1992), with the lack of adequate and appropriate methods for assessing interdisciplinary higher education programs (Field and Lee 1992), with the experiences of graduate students who pursued interdisciplinary studies (Graybill et al 2006), and a successful course approach (Eisen et al 2009). Third, the following essential conditions were identified through the evaluation of two interdisciplinary training programs: participation, training in group skills, information sharing, networking, critical reflection (Gilkey and Earp 2006), participation in a collaborative interdisciplinary team project, and faculty mentors (Misra et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30] In their 2006 discussion of this trend, Choi and Pak offer the following definitions: the interdisciplinary approach "analyzes, synthesizes, and harmonizes links between disciplines into a coordinated and coherent whole." In contrast, a multidisciplinary approach "draws on knowledge from different disciplines, but stays within the boundaries of those fields."…”
Section: A Need For Interdisciplinary and Multidisciplinary Trainingmentioning
confidence: 99%
“…For example, recently Willetts and Mitchell (2016) have proposed a framework for evaluating the dissertation examination process of TD doctoral research, including quality criteria. The potential benefits and barriers of TD training may be similar to those previously identified in interdisciplinary doctoral programs, which in some instances have been defined similarly to TD programs (Graybill et al, 2006;Bosque-PĂ©rez et al, 2016). Graybill and colleagues (2006) found that doctoral students in an interdisciplinary program struggled with academic identity, what to prioritize, and academic productivity.…”
Section: Introductionmentioning
confidence: 67%
“…Six overarching themes emerged from the original 28 themes that were mentioned in two or more of the faculty/ student focus groups at baseline and at five years program differed, so the challenge of providing clear and collective expectations to students was not surprising. Other sources of stress noted in the literature among traditional students included lack of personal time and meeting program deadlines and requirements (Kurtz-Costed et al, 2006;Graybill et al, 2006). Similarly, all three TD cohorts also discussed concerns about having enough time to complete course work, making progress on their research, and having a personal life.…”
Section: Faculty Benefits and Barriersmentioning
confidence: 98%